(untitled) (KULT_online, 2017)
The edited volume Intersektionalität und Forschungspraxis. Wechselseitige Herausforderungen by Mechthild Bereswill, Folkert Degenring, and Sabine Stange addresses the potentialities and limits of implementing the concept ‚intersectionality‘ in empirical research. The disciplinary background of the articles covers the different social sciences and the humanities. The articles represent individual empirical research projects while simultaneously reflecting on their methodological approaches in the analysis of intersecting conditions of inequality.